Betita: Companera y Mentora - Lopez-Garza, Marta (Social justice (San Francisco, Calif.), 2013)
The author recalls meeting Betita for the first time in Santa Monica, where the UCLA Chicano Studies Research Center, run by Juan Gomez-Quinones, held the 'Mexicana/Chicana Women's History International Symposium' in March 1982. Betita presented, along with Marlene Dixon and Ed McCaughan, a fascinating paper on the subject of the economic and social roles of Latinas from a global perspective. In this seminal piece, Betita and her colleagues used a historical class analysis to explore Mexicanas/Chicanas' transnational development within a capitalist, world-system framework. Betita's friendship and mentorship were absolutely crucial for her survival and sanity as a first-generation, college-educated Chicana. Betita was instrumental in influencing her understanding of the world; she enabled her not to feel alone and to believe in herself. Betita was among the very few people who came before her that she could ask for advice and comfort. Adapted from the source document.